Bridging Gender Gap through Technology Based Distance Education: Assessing Mobile Phone and Internet Readiness Level - Amjad Ali Arain (International Islamic University Islamabad, 2019)
Pakistani nation is one of the least literate nations in the world with very high gender parity; in some parts of Pakistan the female literacy rate is the lowest one in the world. This alarming situation is mainly due to the non-availability of and poor accessibility to education. In the era of scientific development this problem can be solved through the application of cost effective technologies. Accessibility to and utility of Information and Communication Technologies (ICTs) are on the rise in Pakistan therefore ICTs in distance education can play an effective role in bridging gender gap. This explanatory study had been designed to investigate into the existing trends and opportunities associated with the utilization of mobile phone and internet in open and distance learning (ODL) to promote female education in Pakistan and in the neighboring countries. Various indicators related to the mobile phone and internet were investigated in order to have an information and in-depth, to explore current trends and to find out practicable ways for the application of ICTs to enhance the accessibility of education for female gender. Quantitative data for this research was accessed from multiple resources: UNdata, the World Data Bank, International Telecommunication Union (ITU), Ministry of Education and Ministry of Communication, country reports, past studies and other useful resource. It was found that ICTs have strengthened significantly since the advent of 21st century. Mobile phones and internet density have also been increasing continuously. Pakistani society has already achieved mobile phone readiness level and internet base has also expanded significantly so it can be the high time to apply these technologies in distance education to achieve the gender parity in education at all levels.